Polish Independent Press Summary, no. 25 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Tygodnik Mazowsze, no. 243 (16 March 1988). Extract from Przegląd Wiadmości Agencyjnych, no. 11 (16 March 1988). Extract from Przegląd Wiadmości Agencyjnych, no. 12 (23 March 1988). Extract from Przegląd Wiadmości Agencyjnych, no. 13 (30 March 1988). Extract from Wola, no. 4(241) (22 February 1988). Extract from KOS, no. 4(134) (21 February 1988). Extract from Solidarność Walcząca - Poznań, no. 6 (21 March 1988). Extract from Region, no. 7 (21 February 1988). Table of Contents from Arka, no. 21 (1988). Extract from Arka, no. 21 (1988). Table of Contents from Nowa Koalicja, no. 4 (1987). Extract from Nowa Koalicja, no. 4 (1987).